ความเชื่อมโยงระหว่างชื่อสีลิปสติกกับสีลิปสติก - ป่านแก้ว ดั่งวิริยะกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This project analyzed associations of lipstick colour names with lipstick colours. Forty observers, 10 males and 30 females, participated in the experiments. Lipstick colour names were divided into four groups: Fruit (Cherry and Watermelon), Flower (Rose and Poppy), Dessert (Red Velvet) and Gems (Ruby). The experiments were done in a darkened room and with a brightness-controlled monitor. Lipstick names were displayed on a monitor one at a time. Observers chose a colour associated with the given name from Color Picker tool, saved and repeated the same procedure until all six names were completed. The monitor was characterized using the GOG model, so that the RGB values could be converted to CIELAB colour values. Colour measurements of the monitor and lipstick samples were done using a spectroradiometer. Based on observers’ experience, observers were divided into three groups: those who never used lipsticks, those who used lipsticks with the particular name and those who used lipsticks with other names. The results showed that observers’ experience on lipsticks usage affected how observers associated lipstick names with lipstick colours. Observers expected colours having higher chroma and lightness than the actual lipsticks with the given names. Moreover, observers expected colours in Flower group with a wider range of hue, chroma, and lightness than the other name groups. The colour names in the same group showed a tendency to have different colour expectations.